On the detection of defects on smooth free metallic paint surfaces. (November 2020) - Guo, Pan; Cao, Pin; Zhang, Pengfei; Chen, Shiwei; Yang, Yongying
Abstract: In view of the difficulty of automatic detection of defects on smooth free metallic paint surfaces, a simple and effective automatic detection system based on deflection principle is proposed in this paper. This system consists of cameras and a set of striped lights. A series of images can be acquired at a certain frequency by camera. And the detection algorithm is divided into three steps. In the first step, the square-difference fusion method and minimum fusion method are used to fuse a group of the standard images to obtain two fusion images, which are used to extract the ROI and partial template. In the second step, partial template is used to perform template matching and correction on the fusion images. In the last step, extraction of mask, extraction of defects, and screening of defects are performed on the corrected fusion image to extract defects. To detect complex metallic paint surfaces of the car, the experimental results demonstrate that the defects detection accuracy can reach 85% and the defect recognition size can reach 0.1mm.